Влияние наночастиц серебра на структуру и механические характеристики пористых сплавов никелида титана - Лариков, Виктор Андреевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The paper presents a study of the effect of additives of silver nanoparticles on the structure and mechanical properties of porous titanium nickelide alloys obtained by the method of self-propagating high-temperature synthesis (SHS). The structure and phase composition of the alloys were studied by X-ray diffraction analysis, scanning and transmission electron microscopy. The mechanical properties of porous alloys have been studied in compression tests.